Hearing loss prevalence and hearing health among school-aged children in the Canadian Arctic. (1st July 2021) - Fitzpatrick, Elizabeth M.; McCurdy, Lynne; Whittingham, JoAnne; Rourke, Ryan; Nassrallah, Flora; Grandpierre, Viviane; Momoli, Franco; Bijelic, Vid
Abstract: Objective: Hearing loss is an important health concern in Canada's Arctic. The objective of this research was to provide information on the prevalence of childhood hearing loss in Nunavut. Design: This cross-sectional study involved comprehensive audiologic assessments of school-aged children in six communities to determine overall and community-specific prevalence of hearing loss. Data were collected about hearing aid use and factors affecting use through a parent questionnaire. Study sample: Assessments were completed for 644 children in kindergarten to grade 6. Results: 124 (19.3%) children had hearing loss of ≥ 30 dB HL at one or more frequencies in at least one ear (93.5% conductive loss). Applying a Canadian prevalence study definition, 148 (23.5%) children had hearing loss. Tympanic membrane perforations were present in 36.8% ( n  = 28) of children with unilateral and 45.8% ( n  = 22) with bilateral loss. Conclusions: The prevalence of hearing loss in Canada's North was almost three times that reported for non-indigenous children. One in five school-aged children was found to have hearing loss that is likely to affect classroom learning and social/emotional development. A hearing health strategy tailored to this population is critically needed.